Analysis of the Effect of Cooling Water Temperature on Thermal Efficiency in the Main Engine of the MV Pritha - Lely Widyaningrum; Agus Prawoto; Dyah Ratnaningsih; Antonius Edy Kristiyono; Intan Sianturi (International Journal of Science and Environment (IJSE), 2026)
Main engines in marine diesel vessels require optimal cooling systems to maintain thermal efficiency amid fluctuating operational loads. This study analyzes the effect of coolant temperature on thermal efficiency of the main engine aboard MV Pritha. Employing a quantitative descriptive-analytic approach, data were collected from operational parameters (RPM, inlet/outlet coolant temperatures, fuel oil consumption) during 12-month sea practice (Sep 2024-Jul 2025). The population comprised all engine data at 70-80% stable load; purposive sampling yielded 30-50 daily observations. Instruments included ship-standard thermometers, flow meters, and tachometers, analyzed via simple linear regression (Y = 64.183 - 0.395X), Pearson correlation (r = 0.995), and ANOVA in SPSS. Results revealed significant negative correlation; 1°C coolant increase temperature reduces thermal efficiency by 0.395% (Sig. < 0.001). Conclusions recommend real-time coolant monitoring and routine maintenance to optimize fuel efficiency and engine longevity.